Studying the Effect of Water on Electrical Conductivity of Carbon Reinforced Aluminum Composite Material - Baghdad Science Journal (مجلة بغداد للعلوم, 2014)
The aim of this study is to understand the effect of addition carbon types on aluminum electrical conductivity which used three fillers of carbon reinforced aluminum at different weight fractions. The experimental results showed that electrical conductivity of aluminum was decreased by the addition all carbon types, also at low weight fraction of carbon black; it reached (4.53S/cm), whereas it was appeared highly increasing for each carbon fiber and synthetic graphite. At (45%) weight fraction the electrical conductivity was decreased to (4.36Scm) and (4.27Scm) for each carbon fiber and synthetic graphite, respectively. While it was reached to maximum value with carbon black. Hybrid composites were investigated also; the results exhibit that minimum value of the electrical conductivity at combination of (45%) weight fraction of fillers, it was (3.49S/cm).The maximum value of electrical conductivity was recorded at 3.5% NaCl solution, it reached (8.82 S/cm) with (45% C. F) for 7 week.